PhET Simulation Software-Problem Based Learning to Improve Physics Concepts on Newton’s Law - Alpi Zaidah; Asrorul Azizi; Hardani Hardani (Jurnal Pembelajaran Fisika, 2022)
The purpose of this action research is to improve students' understanding of basic physics concepts by using the Problem Based Learning model on Newton's law of motion and its application with PhET simulation media. This research is classroom action research with two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects in this study were students of Science Education at the Global Nusantara Education Institute. Data collection techniques with observation and tests. Meanwhile, the data were analyzed using a combination method with a convergent parallel mixed method. Quantitative data analysis with descriptive analysis, data analysis used on qualitative data for data presentation, data presentation, and concluding. The results showed that the use of the Problem Based Learning model with PhET Simulation Media could improve students' understanding of basic physics concepts in Newton's law of motion and its application. The improvement in students' understanding of basic physics concepts is marked by an improvement in the average value of understanding basic physics concepts, namely the average value of students from 36.50 (0%) at the pre-action stage to 63.75 (55%) after the first cycle of action and again increasing after-action cycle 2 with an average value of 84.75 (90%). From these data, it can be seen that the use of the Problem Based Learning model with PhET Simulation Media can improve students' understanding of basic physics concepts.Keywords: Understanding Physics Concepts; Problem Based Learning; PhET Simulation DOI: http://dx.doi.org/10.23960/jpf.v10.n1.202204